THE UTILIZATION OF INSTRUCTIONAL MEDIA IN TEACHING ENGLISH TO SECONDARY SCHOOL STUDENTS: A Qualitative Study at One Junior High School in Bandung - Rahayu, Ria Dewi (2017)
This study is intended to investigate the utilization of instructional media by the teachers to teach secondary school students and the problems faced by the teachers in utilizing instructional media. This study employed qualitative method and the data were obtained through classroom observation and interview. The findings showed that the teachers utilized board, coursebook, picture, realia, video and technology-based presentation as their instructional media for various purposes. This study also discovered that the problems faced by the teachers in utilizing instructional media were the lack of availability of instructional media, teacher's limited time, teacher's lack of knowledge of technology, the difficulty in choosing appropriate instructional media, teacher's difficulty in using instructional media and the technical problems when using instructional media. Considering the findings of the study, this study recommends English teachers to pay more attention to the appropriateness of media with learning objectives, instructional activities, and students' characteristics. Moreover, school and education office are recommended to provide more instructional media and give the teachers workshop or training about the utilization of instructional media in English teaching. Penelitian ini bertujuan untuk mengetahui penggunaan media pembelajaran dalam mengajar bahasa Inggris pada siswa SMP serta masalah yang dihadapi para guru dalam menggunakan media pembelajaran. Penelitian ini menggunakan metode kualitatif dan peneliti menggunakan observasi serta wawancara untuk mengumpulkan data. Hasil penelitian menunjukkan bahwa para guru menggunakan media pembelajaran berupa papan tulis, buku paket, gambar, benda nyata, video, dan media presentasi berbasis komputer untuk berbagai tujuan. Penelitian ini juga menemukan masalah-masalah yang dihadapi para guru dalam menggunakan media pembelajaran. Masalah-masalah yang dihadapi para guru dalam menggunakan media pembelajaran yaitu kurangnya ketersediaan media pembelajaran, keterbatasan waktu, kurangnya pengetahuan para guru mengenai teknologi, kesulitan para guru dalam memilih media pembelajaran yang sesuai, kesulitan para guru dalam menggunakan media pembelajaran di kelas, dan masalah teknis yang muncul saat para guru sedang menggunakan media pembelajaran di kelas. Berdasarkan hasil penelitian, peneliti menyarankan para guru bahasa Inggris untuk lebih memperhatikan kesesuaian media pembelajaran yang digunakan dengan tujuan pembelajaran, kegiatan pembelajaran serta karakteristik siswa. Selain itu, sekolah dan dinas pendidikan diharapkan dapat menyediakan lebih banyak media pembelajaran serta memberikan pelatihan untuk para guru mengenai media pembelajaran untuk mengajarkan bahasa Inggris.